Sosyal değişme açısından cemaat kavramı -Bediüzzaman ve Nurculuk örneği- - Albayrak, Abdullah (My University, 1999)
University of Marmara, Institution of Middle-East and Islamic Countries, Branch of Sociology and Anthropology. The adsiver of this thesis is Dr. İsmail Kara. The first part of my thesis includes Social movements and the concept of religios community (Jemaats). The concepts mentioned in the first part are as a result of both Turkish and western scientists opinion. So this will show the way during my research. The second part is the process of changes in the Turkish society and Jemeats. This process of changes in Turkish society is continuing also and nowadays. Where ever in the world any changes occurred it does not effect only that area but also and other parts of the world. In this part of the thesis also is another important heading is how the Jemaats appeared. The third and the last part of the thesis inclused the biggest movement in Turkey so called Nur Society Movement. The appearance and the guality of this movement are researched separately. These gualities we divided into three group: oriented to persons society and universal
Keywords: DEĞİŞİM; SOSYOLOJİ; Toplumsal değişim